Model bisnis media sosial berbasis cyber citizen journalism pada infosumbar - Agung Praymesa; Sarmiati Sarmiati; Elva Ronaning Roem (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
Infosumbar is a new media originating from West Sumatra which was founded in 2010 starting from a Twitter account named @infoSumbar. Infosumbar then developed into an independent youth media and positioned itself as one of the media that won the trust of the citizens of West Sumatra. Infosumbar utilizes the latest social media platforms that are widely used by young people in conveying various information. This study aims to find out how the citizen journalism-based social media business model at Infosumbar uses a canvas business model which includes nine blocks consisting of value proposition, consumer segments, channels, customer relations, partnerships, key activities, key resources, cost structure and flows. income. The method used in this research is descriptive qualitative method. The results of the study illustrate that Infosumbar has a value proposition, namely as an independent Citizen Journalism-based media, which is offered to clients is advertising services for a product or service to be known by followers of Infosumbar as a whole. Because the current era is still in the digitalization stage, it is not surprising that conventional things have turned to digital. Infosumbar provides an offer so that local brands or advertised brands can receive information to the public. At Infosumbar, in managing customer relations, it uses a door to door model, namely from door to door with a system of picking up customers, not just waiting. The main resources at Infosumbar are people, offices, communication tools, human skills, and creativity. By adding a team, Infosumbar's current revenue stream comes from incoming advertisements. Until now, Infosumbar's key activity is known as citizen journalism-based social media.